Double accessory mental foramina: report of an anatomical variant. (12th September 2014) - Ahmed, S.; Jasani, V.; Ali, A.; Avery, C.
Abstract The presence of accessory mental foramina (AMF) in mandible is a rare anatomical variation. Single accessory mental foramen is reported in a few studies, but double AMF (DAMF) is very uncommon. We present an unusual case of DAMF, with accessory nerves, which were identified during maxillofacial oncology surgery. The nerves were protected by a modified mandibulotomy. It is essential that surgeons to be aware of the possibility of AMF existence and are prepared to take appropriate actions to avoid iatrogenic nerve injury.